The right to a clean and healthy environment in the jurisprudence of European Court of Human Rights and European Court of Justice - Zilic, Lejla (My University, 2018)
Bu uluslararası insan hakları hukuku alanında yeni bir alan araştırmasını sunmaktadır - temiz ve sağlıklı bir çevre hakkı. Uluslararası hukuk çerçevesinde, çevre kanunu - hakların genç bir dalı olarak - yakın zamanda insanlığın karşı karşıya olduğu iklim ve diğer çevre sorunları nedeniyle uluslararası toplumdan büyük ilgi görmüştür. Avrupa İnsan Hakları Mahkemesinin uygulamasında gelişen Avrupa kıtasal hukuk sisteminin insan hakları sistemi, temiz ve sağlıklı bir çevreye açık bir hak olduğunu hala bilmemektedir. Temiz ve sağlıklı birçevreye ilişkin bazı hakların ihlaline ilişkin davalar, Avrupa Mahkemesinde Avrupa Sözleşmesinde açıkça tanınan diğer haklar dahilinde incelenir. Ayrıca, Avrupa Birliği, Avrupa'daki bir suigeneris örgütü olarak, temiz ve sağlıklı bir çevreye açık bir hak olduğunu da kabul etmemektedir. Uygulamada, Avrupa Adalet Divanı temel olarak Üye Devletlerin çevre koruma alanındaki yükümlülüklerini geliştirmektedir. Bu yüksek lisans tezinin amacı, bumahkemenin çevre hukuku ve insan hakları arasında nasıl bir bağ oluşturduğunu göstermek için Avrupa Ġnsan Hakları Mahkemesi'nin içtihadını incelemektir. Temiz ve sağlıklı çevre hakkının dolaylı olarak korunmasıyla, bu Mahkeme çevre hukuku ve insan haklarına yeni bir yaklaşım getirmektedir. Buna ek olarak, Avrupa Adalet Divanı'nın uygulamasını inceler ve Avrupa Birliği'nin çevre sorunlarına nasıl yaklaştığını analiz etmeyi amaçlar. Buna göre, bu makalenin ana hipotezi, temiz ve sağlıklı bir çevre hukuku sahip olmanın temel bir insan hakkı olarak tanınması ve Avrupa Konvansiyonu tarafından açıkça korunmasının sağlanmasıdır. Ayrıca, yüksek lisans tezinin bir bölümü, insan haklarının korunması ve tek tek ülkelerin anayasaları için karşılaştırmalı sistemlerde temiz ve sağlıklı bir çevre hakkının araştırılmasına ayrılmıştır. Bu araştırmanın amacı uluslararası toplumun insan hakları olarak temiz ve sağlıklı bir çevreyi koruma çabalarını göstermektir.

This master's thesis presents the research of a new field in international human rights law - the right to a clean and healthy environment. Within the framework of international law, environmental law - as relatively young branch of rights - has recently attracted great attention from the international community due to climate and other environmental problems facing mankind. The human rights system of the European continental legal system, which evolves in the jurisprudence of the European Court of Human Rights, still does not recognize the explicit right to a clean and healthy environment. Cases concerning violation of some aspects of the right to a clean and healthy environment are examined by the European Court within other expressly recognized rights in the European Convention. Furthermore, the European Union, as a sui generis organization in Europe, also does not recognize the explicit right to a clean and healthy environment. In its practice, the European Court of Justice mainly develops obligations of Member States in field of environmental protection. The aim of this master's thesis is to examinethe jurisprudence of the European Court of Human Rights in order to illustrate how this court creates a link between environmental law and human rights. By the indirect protection of the right to clean and healthy environemnt, this Court makes a new approach to environmental law and human rights. In addition, the master's thesis explores the jurisprudence of the European Court of Justice and aims to analyze how the European Union approaches environmental issues. Accordingly, the main hypothesis of this paper is that the right to a clean and healthy environment should be recognized as a fundamental human right and explicitly protected by the European Convention. Additionally, one part of the master's thesis is devoted to the research of the right to a clean and healthy environment in comparative systems for the protection of human rights and the constitutions of individual countries. The goal of this research is to illustrate the efforts of the international community to protect the right to a clean and healthy environment as human right.
Keywords: Avrupa Adalet Divanı; Avrupa Ġnsan Hakları Mahkemesi; Avrupa İnsan Hakları Mahkemesi; Çevre hukuku, Uluslararası; Environmental law, International; European Court for Human Rights; European Court of Human Rights; European Court of Justice; humanrights; insan hakları; international environmental law; right to a clean and healthy environment; temiz ve sağlıklı bir çevre hukuku; uluslararası çevre hukuku